Islamic Ethics as the Antithesis of Manipulation Culture: A Critical Study on the Failure of Trust (Amanah) in Financial Reporting Practices - Haryani, Sri; Alimuddin, Alimuddin; Darwis, Darwis (Amkop Management Accounting Review (AMAR), 2025)
This study aims to deconstruct the hegemony of manipulation culture in global and national financial reporting practices occurring over the past decade. It proposes Islamic Ethics as a fundamental antithesis to restore accounting integrity. This research employs a non-positivist paradigm with a critical study approach. Data analysis was conducted using the dialectical method to juxtapose the reality of manipulation (thesis) against Islamic values (antithesis) to generate a new synthesis. The critical analysis identifies three dimensions of the failure of amanah (trust). First, ontologically, modern financial statements have become entrapped in a simulacrum (hyperreality); Islamic ethics deconstructs this through the concepts of al-haqq and the prohibition of tadlis, demanding that financial statements serve as a document of syahadah (testimony). Second, epistemologically, the instrumental rationality of homo economicus has proven ineffective at preventing fraud; Islam offers the epistemology of muraqabah (inherent divine supervision), which dismantles the rationalization of fraud. Third, axiologically, the hegemony of profit maximization is replaced by the synthesis of barakah (blessing) based on maslahah as an indicator of sustainable performance. This research concludes that a shift from horizontal accountability to Transcendental Accountability is necessary. The accounting profession must transform from mere record-keepers into guardians of amanah who hold their integrity accountable to God, transcending mere compliance with formal regulations.